The microstructure of coaching practice: behaviours and activities of an elite rugby union head coach during preparation and competition - Hall, E. T.; Gray, S.; Sproule, J. (Journal of Sports Sciences, 2016)
The activities and behaviours of a female head coach of a national rugby union team were recorded in both training and competition, across a whole rugby season, using the newly developed Rugby Coach Activities and Behaviours Instrument (RCABI). The instrument incorporates 24 categories of behaviour, embedded within three forms of activity (training form (TF), playing form (PF) and competitive match) and seven sub-activity types. In contrast to traditional drill-based coaching, 58.5% of the training time was found to have been spent in PF activities. Moreover, the proportion of PF activities increased to a peak average of 83.8% in proximity to the team`s annual international championship. Uniquely, one of the coach`s most prolific behaviours was conferring with associates (23.3%), highlighting the importance of interactions with assistant coaches, medical staff and others in shaping the coaching process. Additionally, the frequencies of key behaviours such as questioning and praise were found to vary between the different activity forms and types, raising questions about previous conceptions of effective coaching practice. The findings are discussed in the light of the Game Sense philosophy and the role of the head coach.